Comparative evaluation of immunomodulatory cytokines for oncolytic therapy based on a high-efficient platform for oHSV1 reconstruction - Yingzheng Gao; Yufang Zou; Changjing Wu; Juan Tao; Zuqing Nie; Jinyuan Yan; Pengfei Wang; Xinwei Huang (Virology Journal)
Abstract Background Triple-negative breast cancer (TNBC) presents significant therapeutic challenges due to its immunosuppressive tumor microenvironment (TME). Oncolytic herpes simplex virus type 1 (oHSV1) offers dual mechanisms of tumor lysis and immune activation, yet the optimal cytokine payloads for TNBC remain undefined. Methods We developed a CRISPR/Cas9-mediated platform for high-efficiency oHSV1 engineering, replacing the ICP47 locus with murine IFN-γ, GM-CSF, or IL-15Rα/IL-15 fusion protein (IL15Fu). Constructs were validated for cytokine secretion, MHC modulation, and cytotoxicity in 4T1 TNBC and a panel of human cancer cell lines. Antitumor efficacy and immune remodeling were evaluated in a syngeneic 4T1 model using RNA sequencing and flow cytometry. Results The CRISPR platform achieved 62.5–71.4% homologous recombination efficiency, enabling rapid virus construction. In vitro, OV-IFNG exhibited upregulated MHC I/II expression and potent cytotoxicity, while OV-GMCSF attenuated oncolysis in subsets of breast cancer cell lines. In the 4T1 model, OV-IL15Fu modestly improved tumor control and extended survival without apparent toxicity, while OV-IFNG induced early mortality associated with systemic toxicity. Transcriptomic profiling revealed divergent immune modulation: OV-IL15Fu enriched T cell/NK cytotoxicity pathways, OV-IFNG amplified cytokine/chemokine signaling, and OV-GMCSF paradoxically enhanced myeloid recruitment while inhibiting MHC-II pathways. Flow cytometry confirmed functional differences in immune activation: OV-IL15Fu expanding cytotoxic lymphocytes (CD8⁺ T/NK cells), OV-IFNG preferentially promote Th1 polarization and innate immune activation, and OV-GMCSF failed to activate T cells despite myeloid infiltration. Conclusions Our findings underscore the need for rational cytokine selection in oHSV1-based immunotherapy. While IFN-γ increased immunogenic markers, its systemic toxicity and myeloid effects may limit benefit. GM-CSF exacerbated immune suppression in this context, whereas IL15Fu showed favorable immunostimulatory properties without detectable toxicity. These data support IL15Fu as a contextually promising payload for further evaluation in TNBC-targeted oncolytic virotherapy.